Program Bimbingan Belajar Gratis untuk Siswa dari Keluarga Kurang Mampu - Jufri; Azizah, Laelah; Kurniati Asri, Wahyu; Mannahali, Misnah; Dalle, Ambo (Program Studi Manajemen FEB UNM, 2024)
The Free Tutoring Program for Students from Underprivileged Families aims to enhance access to and quality of education for students from economically disadvantaged backgrounds. The program includes the identification and selection of students, recruitment and training of tutors, development of learning materials and modules, implementation of tutoring sessions, as well as regular monitoring and evaluation. A total of 100 students from various elementary and secondary schools were selected to participate in this program. Tutors, consisting of college students, teachers, and volunteers, received intensive training to ensure the quality of the tutoring provided. The learning materials, based on the national curriculum, were adapted to the students' needs, covering core subjects and additional skills. The results of the program showed significant improvements in students' academic performance, increased motivation to learn, and enhanced self-confidence in their studies. The interactive and personalized tutoring sessions successfully created a conducive learning environment. Regular monitoring and evaluation ensured the program ran effectively and provided useful feedback for improvement. The provision of motivation and rewards also proved effective in maintaining students' enthusiasm for learning. The program demonstrated that through solid collaboration between various parties, including schools, education departments, and the community, as well as structured program implementation, students from underprivileged families can achieve better academic performance and have broader opportunities for their future. Suggestions for the sustainability of this program include expanding the program's scope, enhancing tutor training, developing digital modules, strengthening collaboration with the community, and continuous evaluation. Thus, this program is expected to continue contributing significantly to improving access to and quality of education for students from underprivileged families.